Penerapan Jalan Kaki Dua Puluh Menit Terhadap Perubahan Tekanan Darah Pada Lansia Penderita Hipertensi Di Desa Dukuh Jati - Agustina Nur Istiqomah; Dewi Kartika Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: The world’s elderly population is predicted to increase very quickly in 2020. Based on Susenas and Sakernas data, namely 12,2% in 2020 to 12,71% in 2021.The aging process will affect physical and mental changes in the elderly which results in a decrease in body resistance so that it is susceptible to various diseases and the most common is hypertension. Purpose: To determine changes in blood pressure in elderly patients with hypertension before and after walking activities. Methods: This application uses a descriptive case study by observing 2 female respondents aged 61-64 years who are given the implementation of walking for 20 minutes. Result: After the application of walking for 20 minutes for 3 consecutive days a week there was a decrease in blood pressure. Responden 1 with an average decrease in systolic pressure of 1 mmHg, diastolic 3 mmHg. Responden 2 average decrease in systolic blood pressure 2,3 mmHg, diastolic 0,6 mmHg. Conclusion: Walking for 20 minutes for 3 days a week can reduce blood pressure in elderly people with hypertension.